Clinical and tree hollow populations of human pathogenic yeast in Hamilton, Ontario, Canada are different. Issue 5 (28th November 2013) - Carvalho, Chris; Yang, Jiaqi; Vogan, Aaron; Maganti, Harinad; Yamamura, Deborah; Xu, Jianping
Summary Yeast are among the most frequent pathogens in humans. The dominant yeast causing human infections belong to the genus Candida and Candida albicans is the most frequently isolated species. However, several non‐C. albicans species are becoming increasingly common in patients worldwide. The relationships between yeast in humans and the natural environments remain poorly understood. Furthermore, it is often difficult to identify or exclude the origins of disease‐causing yeast from specific environmental reservoirs. In this study, we compared the yeast isolates from tree hollows and from clinics in Hamilton, Ontario, Canada. Our surveys and analyses showed significant differences in yeast species composition, in their temporal dynamics, and in yeast genotypes between isolates from tree hollows and hospitals. Our results are inconsistent with the hypothesis that yeast from trees constitute a significant source of pathogenic yeast in humans in this region. Similarly, the yeast in humans and clinics do not appear to contribute to yeast in tree hollows.